Penang Chinese Customs and Traditions - Goh Sang Seong, (Kajian Malaysia, 2015)
The Chinese first settled in Penang about two centuries ago bringing along with them their cultural practices from China. However, with the passing of time their cultural practices had undergone significant changes especially among the Hokkien Chinese who comprise the majority of the Chinese community in Penang. This essay examines the customs and traditions of the Penang Chinese from the aspects of beliefs and prayer ceremonies, festive celebrations, artefacts and daily activities in a more comprehensive manner. The influences of modern education and geographical environments have resulted in the evolution of their own unique and distinctive variation of Chinese customs. Their festive celebrations, beliefs, practices and daily activities reveal the inheritance from their ancestors from China besides the incorporation of Malay sociocultural elements. In fact, some customs are peculiar only to the Penang Hokkien who had to survive in an environment that was different from China although these customs are still based on traditional Chinese concepts and philosophy. The difference is the way in which these customs and traditions are celebrated. Present day Penang Chinese remain loyal to traditional customs brought by their ancestors from China although there is evidence of assimilation with Malay elements.